Ang Pagkukuwento bilang Pagbabalik-Loob: Pagdalumat sa Halaga ng “Awit ng Matandang Marinero” ni Samuel T. Coleridge sa Talambuhay ni Fr. Roque Ferriols, S.J - De Joya, Preciosa Regina A (Archīum Ateneo, 2018)
At the beginning of Roque Ferriols’s autobiography, he remembers the night when he and his father read Samuel T. Coleridge’s “Rime of the Ancient Mariner,” and particularly, how his father translated the English verses to Filipino. This essay explores the significance of Coleridge’s long poem to Ferriols’s reflection on the purpose and structure of his own autobiographical writing, showing how storytelling is not only a means of atonement towards personal salvation but a process in which reconciliation and re-connection with the community can be achieved. Furthermore, I relate Ferriols’s account of the translation of Coleridge’s poem to the philosopher’s effort at coming to terms with the controversies of the Filipinization movement in the 1970s.